(untitled) (Research, Society and Development, 2023)
This study aims to identify the scientific production about the impacts on the mental health of nursing professionals related to their work in intensive care units for the treatment of COVID-19. This is an integrative literature review whose data collection took place in January 2023 from the databases Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), MEDLINE and Scientific Electronic Library Online (SCIELO). To search for articles, the following descriptors were used: “intensive care unit AND COVID-19 AND nursing AND mental health” and “Intensive Care Units AND COVID-19 AND Nursing AND Mental Health”. Eleven articles were selected as corpus for analysis. It was found that the work overload, the shortage of trained professionals to work in intensive care units, the need for constant updating of professionals, the fear of contamination themselves, of family members and society, the stigma related to the disease, as well as the large number of deaths were factors that directly affected the mental health of nursing professionals. An increase in levels of anxiety, stress, depression and post-traumatic stress disorder was also identified during the work of nursing professionals in intensive care units for COVID-19. Based on the results obtained, it is observed that it is necessary to formulate occupational health policies that seek to minimize the mental burden of nursing professionals.